Atypical locations for cystic lymphangiomas - Ioanna Gkalonaki; Michalis Anastasakis; Ioannis Patoulias (Elsevier, 2022)
The aim of the present study is to highlight 7 cases with rare localized cystic lymphangiomas (CLs) and to present the concerns regarding their management.During the period 2015-2021, 7 children between 4 months and 11 years old with CL, with a diameter of 2.5-7 cm, were managed in our clinic. The rare locations involve the chest wall, the abdominal wall (2/7), the femoral region, the epididymis, the forearm and the great omentum. In one case a progressively increasing lesion observed by the parents resulted in the surgical evaluation. In 3 cases there was a sudden increase in size, in 2 the diagnosis was accidental, while one had a prenatal finding. We performed an elective surgery, under general anesthesia and the cystic lesion was removed clearly defined. The diagnosis was established histologically.The patients had an uneventful postoperative course and were discharged home on postoperative day 1. In a follow-up period of 18 months no recurrence occurred.CLs with atypical locations usually escape attention prenatally, and are diagnosed at an older age, after an injury or inflammation. Surgical excision is considered the treatment of choice. Sclerotherapy shall be used in the recurrence of a resected and histologically documented CL.